Literature Review on the Development of an AI-Based Humanoid Chatbot for UII IT Centrum Services - Rafa Radhitya Riyanto; Rahadian Kurniawan (Jurnal Teknologi Informatika dan Komputer, 2026)
In this literature review, chatbots and their use in digital marketing and promotion have been thoroughly studied in 2024 to 2026. In a literature review of 20 main references, chatbot technology has evolved from service-driven systems to humanistic ones with help from humanoid chatbots and anthropomorphic AI. In 2024 starting from reactive automation to macro digital transformation, then into the public sector and in 2026 ended with emotional closeness. Large Language Models (LLM) technologies such as GPT and multimodal artificial intelligence are the key platforms to make the interaction more natural and contextually sensitive. The review concludes that chatbots are not simply automation tools but are key strategic factors for the digital economy ecosystem to improve efficiency, build customer relationships and drive promotion for the consumer. The literature review is also used as the main theoretical foundation in the author’s thesis to design and expand the first AI-based chatbot system for the UII IT Centrum information services.